BEST STRATEGIES FOR THE IDEAL BUSINESS MODEL - Dimitrios VALSAMIDIS; Dimosthenis PAPPAS; Vasilios FERELIS; Michael NIKOLAIDIS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2018)
In different chronological periods, four innovative web based business models proved that the human creativity can lead to huge success even with few resources in the beginning. All the examples have something common, the rapid implementation of an instant inspiration. The so called big four (Facebook, Amazon, Google, Apple) or FAGA or GAFA have explosive success in a certain period of time. The last decade, Amazon, Apple, Facebook and Google are the four most influential companies on the planet. These companies excel via their superior use of technology, have built incredible ecosystems and have embraced partnerships and external innovation. Beyond all of this, the big four have embraced an entirely new way of doing business: (1) They are rooted in equally powerful technologies—and their intelligent usage. In other words, they differ from traditional platforms in that they are not predicated on physical assets, land, and natural resources. (2) They benefit tremendously from vibrant ecosystems (partners, developers, users, customers, and communities). Facebook in social networks, Amazon in electronic commerce, Google in search engines and Apple in the multimedia devices proved that brand and business model work together because if they do not align brand and business model it will backfire, probably not in the short run but surely in the long run. The similarities and the differences of the big four models can assist to draw useful insights about the necessary guidelines for an effective entrepreneurship. Using these examples, we conduct a comparative evaluation using SWOT analysis and business model canvas, and present the results. The best practices of FAGA draw valuable insights for an ideal business model.